Comparative empirical analysis of financial intermediation systems in Central and Eastern Europe - Bożena Horbaczewska (International Journal of Management and Economics, 2019)
The purpose of this paper is to evaluate the level of similarity between financial systems in selected Central and Eastern European countries (CEE11) and four models of capitalism in Western Europe identified by B. Amable [The diversity of modern capitalism, 2003]. A comparative analysis in this institutional area was done on the basis of six variables. Three of them represent inputs, that is, institutional determinants, and other three variables describe outputs of institutional regulations. For each of them coefficients of similarity between a CEE11 country and a selected Western European country were calculated, and based on it the similarity hexagons were created. In this paper, two pictures of the institutional arrangements were taken: for 2005 and for 2014. Additionally, an analysis of changes that took place in institutional solutions in the CEE11 countries, based on the variables and the coefficients of similarity, was carried out. The analyses showed that in the area of financial intermediation, the group of CEE11 countries in 2005 was characterized by the greatest similarity to the Continental model of capitalism. The same investigations carried out for 2014 indicate a significant shift in the analyzed area toward solutions typical of the Mediterranean model.
Keywords: P51; 650; financial systems; comparative empirical study; Central and Eastern Europe